(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the term asymmetry and its use, changes in the relationship between form and content, the attitude of different scholars to them, the level of content and expression in language, and changes in language. The ideas are scientifically based on various examples, including the concepts of asymmetric dualism, functional transposition, and serious analysis. It has been shown that the problem of migration also exists in the structure of morphemes and is still applicable today. Functional transposition, on the other hand, is now practiced within word families and is almost never used at the level of morphemes.